Techno-economic analysis and decision making for PHEV benefits to society, consumers, policymakers and automakers - Al-Alawi, Baha Mohammed, author; Bradley, Thomas, advisor; Duff, William, advisor; Olsen, Daniel, committee member; Zimmerle, Dan, committee member; Labadie, John, committee member (Colorado State University. Libraries, 2012)
Plug-in hybrid electric vehicles (PHEVs) are an emerging automotive technology that has the capability to reduce transportation environmental impacts, but at an increased production cost. PHEVs can draw and store energy from an electric grid and consequently show reductions in petroleum consumption, air emissions, ownership costs, and regulation compliance costs, and various other externalities. Decision makers in the policy, consumer, and industry spheres would like to understand the impact of HEV and PHEV technologies on the U.S. vehicle fleets, but to date, only the disciplinary characteristics of PHEVs been considered. The multidisciplinary tradeoffs between vehicle energy sources, policy requirements, market conditions, consumer preferences and technology improvements are not well understood. For example, the results of recent studies have posited the importance of PHEVs to the future US vehicle fleet. No studies have considered the value of PHEVs to automakers and policy makers as a tool for achieving US corporate average fuel economy (CAFE) standards which are planned to double by 2030. Previous studies have demonstrated the cost and benefit of PHEVs but there is no study that comprehensively accounts for the cost and benefits of PHEV to consumers. The diffusion rate of hybrid electric vehicle (HEV) and PHEV technology into the marketplace has been estimated by existing studies using various tools and scenarios, but results show wide variations between studies. There is no comprehensive modeling study that combines policy, consumers, society and automakers in the U.S. new vehicle sales cost and benefits analysis. The aim of this research is to build a potential framework that can simulate and optimize the benefits of PHEVs for a multiplicity of stakeholders. This dissertation describes the results of modeling that integrates the effects of PHEV market penetration on policy, consumer and economic spheres. A model of fleet fuel economy and CAFE compliance for a large US automaker will be developed. A comprehensive total cost of ownership model will be constructed to calculate and compare the cost and benefits of PHEVs, conventional vehicles (CVs) and HEVs. Then a comprehensive literature review of PHEVs penetration rate studies will be developed to review and analyze the primary purposes, methods, and results of studies of PHEV market penetration. Finally a multi-criteria modeling system will incorporate results of the support model results. In this project, the models, analysis and results will provide a broader understanding of the benefits and costs of PHEV technology and the parties to whom those benefits accrue. The findings will provide important information for consumers, automakers and policy makers to understand and define HEVs and PHEVs costs, benefits, expected penetration rate and the preferred vehicle design and technology scenario to meet the requirements of policy, society, industry and consumers.
Keywords: CAFE; electric power; energy; hybrid cars; total cost of ownership; transportation